2013
DOI: 10.4315/0362-028x.jfp-13-119
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Virulence Profiles of Salmonella Isolated from Butcher Shops in Minas Gerais, Brazil

Abstract: Salmonella can contaminate finished products of butcher shops, mainly through cross-contamination of utensils exposed to raw materials. To identify the main sources of contamination with this foodborne pathogen in four butcher shop environments, surface samples were obtained from employees' hands, cutting boards, knives, floor of the refrigeration room, meat grinders, and meat tenderizers (32 samples per area) and analyzed for Salmonella using the International Organization for Standardization method 6579, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…from freshwater fish which are not exposed to antibiotic pressure compared to poultry. The resistance pattern of clindamycin was similar to the observation of Cossi et al who also found all isolates in their study resistant to clindamycin [40]. The results of colistin are in disagreement with Osman et al who found most of their isolates sensitive to colistin while we recorded a higher percentage of resistance [41].…”
Section: Discussionsupporting
confidence: 76%
“…from freshwater fish which are not exposed to antibiotic pressure compared to poultry. The resistance pattern of clindamycin was similar to the observation of Cossi et al who also found all isolates in their study resistant to clindamycin [40]. The results of colistin are in disagreement with Osman et al who found most of their isolates sensitive to colistin while we recorded a higher percentage of resistance [41].…”
Section: Discussionsupporting
confidence: 76%
“…However, isolates resistant to trimethoprim-sulfamethoxazole, sulfamethoxazole, and tetracycline were detected in cutting boards of butcher shops from Minas Gerais State (SE). All isolates were susceptible to amikacin and cefotaxime [129].…”
Section: Streptococcus Sppmentioning
confidence: 99%
“…Few Salmonella sp. isolates have been evaluated for antimicrobial resistance due to low levels of their detection in carcasses, production line, and slaughterhouse environment [127][128][129][130]. Salmonella sp.…”
Section: Streptococcus Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…A culture collection composed of 79 Salmonella isolates was considered in the present study. All isolates were obtained from previous studies from different steps of the beef and pork processing chain (Table 1; Bersot, 2005;Cossi et al, 2013;Cossi et al, 2014). All isolates were previously identified by serological reactions (Fiocruz, Rio de Janeiro, RJ, Brazil) and stored at − 20°C in tripticase soya broth (TSB, Oxoid Ltd., Basingstoke, England) added to glycerol 20% (v/v).…”
Section: Microorganismsmentioning
confidence: 99%